Consumer Behavior: Description of E-Banking Post-Usage - Intan Permana (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
Digitization in banking to the cashless society by providing as non-cash transactions. In other hand a result of survey showing the low penetration of internet usage for online money transfer as wrong banking services. This article, has a purpose describe post-usage behavior. The author uses a descriptive design to solve the problem of low penetration of internet users for online money transfers. Today, e-banking services are considered as one of the factors that the customer expressed loyal to the banking services.